2005
DOI: 10.1007/s11373-005-9033-y
|View full text |Cite
|
Sign up to set email alerts
|

Antineural antibody in patients with Tourette’s syndrome and their family members

Abstract: SummaryIt has been proposed that antineural antibodies were present in patients with Tourette's syndrome (TS) and other neuropsychiatric disorders. The purpose of our study was to investigate the presence of antineural antibodies in the individuals with Tourette's syndrome and the family members of TS patients. The sera of four TS patients with no current streptococcal infection, their tic-free family members including father, mother and sibling, and a age-matched control group who were tic free were assayed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…It is currently quite well known that there are positive antibasal ganglia antibodies [14] and prominent antineural antibodies in TS patients and in first-generation family members [17]. Our report presents evidence that there is a broad alteration in immune function, and this dysregulation in cellmediated immunity is seen in addition to altered functions of the neurocognitive functions of the brain.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…It is currently quite well known that there are positive antibasal ganglia antibodies [14] and prominent antineural antibodies in TS patients and in first-generation family members [17]. Our report presents evidence that there is a broad alteration in immune function, and this dysregulation in cellmediated immunity is seen in addition to altered functions of the neurocognitive functions of the brain.…”
Section: Discussionsupporting
confidence: 49%
“…Others have also reported the prevalence of elevated ASO coupled with positive antibasal ganglia antibodies (ABGA), which were observed more often in TS than other central nervous system diseases, or when comparing patients presenting with TS and healthy controls without TS diagnosis [14,17]. Moreover, genetic susceptibility or familial inheritance may explain the observations of a higher rate of TS in relatives of patients with TS and the observation that only certain subgroups of the general population manifest the symptoms associated with TS following streptococcal infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarities to autism include a heterogeneous phenotype, a male to female bias of 3-4:1 and strong genetic etiology (Jankovic, 2001). These children are of interest due to evidence that autoimmune mechanisms could be involved in the neuropathology of Tourette Syndrome (Kiessling, Marcotte, & Culpepper, 1993;Swedo et al, 1998;Yeh et al, 2006). In the study of Tourette Syndrome, two groups have demonstrated an antibody-mediated involvement by the induction of disease in rats after intracerebral injection of immunoglobulin (Ig) G or serum from patients with Tourette Syndrome (Hallett, Harling-Berg, Knopf, Stopa, & Kiessling, 2000;Taylor et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the similarities between Tourette syndrome and autism include an unknown etiology, a heterogeneous phenotype, a male to female bias of 3:1, the presence of repetitive behaviors and the importance of genetic factors (Jankovic, 2001). Evidence that autoimmune mechanisms could be involved in the neuropathology of Tourette syndrome also makes these subjects an interesting positive control group (Jankovic, 2001;Kiessling, Marcotte, & Culpepper, 1993;Singer et al, 1998;Swedo et al, 1998;Yeh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%